Statistical performance of single sinusoid frequency estimation in white noise using state-variable balancing and linear prediction - Kot, A.; Parthasarathy, Sarangarajan; Tufts, D.; Vaccaro, R. (IEEE Transaction on Acoustics, Speech and Signal Processing, 1987)
This correspondence presents a statistical analysis of frequency estimation using state-variable balancing for a single sinusoid in the presence of additive noise at high signal-to-noise ratios. The calculated variance is compared to the performance of the frequency estimation using linear prediction and the result is validated by simulations.